2019
DOI: 10.1111/1467-8489.12311
|View full text |Cite
|
Sign up to set email alerts
|

The effect of land use regulations on farmland protection and non‐agricultural land conversions in China

Abstract: This paper examines the effect of the Prime Farmland Protection Regulation in protecting high quality farmland from urban development and the subsequent effect on non‐farmland conversion in China in the first decade after the Regulation came into effect (1995‐2005). The empirical evaluation is conducted with geo‐referenced panel data for the entire country. Results indicate that the rate of farmland conversion was reduced during 1995‐2000. About two‐fifths of the reduction results from the protection of farmla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Simultaneously, the Chinese Government has successively issued notices on handling land violation cases and prohibiting cultivated land abandonment in development zones and urban construction. After that, the necessary regulations on cultivated land protection were formed in 1994, and a preliminary idea of the dynamic balance of total cultivated land was proposed in 1996 (Li, 2019; Wu, Shan, Guo, & Peng, 2017). On this basis, the connotation, policies, and regulations of China's cultivated land protection are becoming more and more perfected.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the Chinese Government has successively issued notices on handling land violation cases and prohibiting cultivated land abandonment in development zones and urban construction. After that, the necessary regulations on cultivated land protection were formed in 1994, and a preliminary idea of the dynamic balance of total cultivated land was proposed in 1996 (Li, 2019; Wu, Shan, Guo, & Peng, 2017). On this basis, the connotation, policies, and regulations of China's cultivated land protection are becoming more and more perfected.…”
Section: Introductionmentioning
confidence: 99%
“…Subiyanto and Fadilla [56] analyzed urban expansion in Indonesia and reported an increase in urban areas between 2005 and 2017, while farmland, grassland, and wetlands declined. Li [57] assessed regulations for farmland conservation in China. Although it could not provide direct evidence, the study reported that farmland increased during the study period, but forest area decreased.…”
Section: Prediction Results and The Effectiveness Of Local Regulationmentioning
confidence: 99%
“…However, considering quick farmland loss during recent decades due to urban sprawl and very limited lands suitable for expanding the farmland area, more strict protection of the current farmland is still very necessary. To this end, the Chinese government has implemented several policy measures to strictly control the farmland occupation of non-agricultural construction, and to regulate the farmland protection and ecological restoration [40,41].…”
Section: Implications For Farmland Protectionmentioning
confidence: 99%